2017
DOI: 10.1016/j.ydbio.2016.05.023
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the functions of nonclassical MHC class Ib genes in Xenopus laevis by the CRISPR/Cas9 system

Abstract: A large family of highly related and clustered Xenopus nonclassical MHC class Ib (XNC) genes influences Xenopus laevis immunity and potentially other physiological functions. Using RNA interference (RNAi) technology, we previously demonstrated that one of XNC genes, XNC10.1, is critical for the development and function of a specialized innate T (iT) cell population. However, RNAi limitation such as a variable and unstable degree of gene silencing in F0 and F1 generations is hampering a thorough functional anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 56 publications
0
18
0
Order By: Relevance
“…S6). The relatively high degree of mosaicism within individual F 0 tadpoles has been previously reported and is likely due to a rapid embryogenesis and continuous CRISPR/Cas9-mediated genome modifications after the one-cell embryo stage, which results in independent doublestrand breaks with different mutations upon imprecise DNA repair mechanism (22). To evaluate the potential off-target effects on Jα segments proximal to, or sharing sgRNA motifs with Jα1.14, we sequenced three Jα gene segments in the three tadpoles carrying the highest number of Jα1.14 mutations and did not find any off-target mutations (SI Appendix, Fig.…”
Section: Targeted Disruption Of Ivα45 T Cells Using Two Different Revmentioning
confidence: 80%
See 1 more Smart Citation
“…S6). The relatively high degree of mosaicism within individual F 0 tadpoles has been previously reported and is likely due to a rapid embryogenesis and continuous CRISPR/Cas9-mediated genome modifications after the one-cell embryo stage, which results in independent doublestrand breaks with different mutations upon imprecise DNA repair mechanism (22). To evaluate the potential off-target effects on Jα segments proximal to, or sharing sgRNA motifs with Jα1.14, we sequenced three Jα gene segments in the three tadpoles carrying the highest number of Jα1.14 mutations and did not find any off-target mutations (SI Appendix, Fig.…”
Section: Targeted Disruption Of Ivα45 T Cells Using Two Different Revmentioning
confidence: 80%
“…2): (i) the disruption of the Jα1.14 gene segment by the CRISPR/Cas9 genome editing system to prevent the iVα45-Jα1.14 TCR rearrangement; and (ii) I-SecI meganucleasemediated transgenesis targeting the CDR3 region to silence the Vα45-Jα1.14 rearrangement. We have shown that the CRISPR/ Cas9 system is a robust method for targeting with high specificity a single member of multigene families in X. laevis (22). Accordingly, we designed a single guide RNA (sgRNA) against the Jα1.14 gene ( Fig.…”
Section: Targeted Disruption Of Ivα45 T Cells Using Two Different Revmentioning
confidence: 99%
“…CRISPR gene editing is new in the allotetraploid X. laevis (Lane et al 2015;Wang et al 2015;Jaffe et al 2016;Banach et al 2017), and tissue-targeted CRISPR knockouts have not been reported. Our results indicate that CRISPR can efficiently target a tissue of interest.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to a single classical MHC class I gene per genome, X. laevis has a large family of MHC class I-like genes ( mhc1b or previously known as XNC) , which are clustered outside the MHC locus [53, 54]. mhc1b genes encode molecules with the typical three immunoglobulin α domain structure, exhibit low polymorphism, and in general have limited tissue distribution [53, 55].…”
Section: Mhc Class I and Class I-like Molecules In Tumor Immunitymentioning
confidence: 99%